Psychometric properties of the Portuguese version of the invalidating childhood environment scale - Vieira, Ana Isabel (2018)
Purpose The current study aimed to examine the psychometric properties of the Portuguese version of the invalidating childhood environment scale (ICES) in a non-clinical and clinical sample of eating disorder (ED) patients. This study also investigated the between-sample differences regarding invalidating parental behaviors and family styles and explored the associations between invalidating childhood environments and eating pathology. Methods A sample of 410 high school and college students and 101 patients with a diagnosis of ED completed self-report measures. Principal component analyses and confirmatory factor analyses were conducted to examine the factor structure of the ICES. The internal consistency and the between-sample differences and associations between invalidating childhood environments and eating pathology were also tested. Results Principal component analyses and confirmatory factor analyses indicated a two-factor solution for each parent. The ICES demonstrated high internal consistency and was able to differentiate between non-clinical and clinical samples. The perception of parental invalidation was higher in ED patients, and the clinical sample presented higher scores in the chaotic and perfect family styles and lower scores in the validating family style, in comparison with the non-clinical sample. Both maternal invalidation and invalidating styles were significantly associated with a higher ED symptomatology. Conclusions The Portuguese version of the ICES revealed adequate psychometric properties. Considering the relationship between invalidation in family and eating pathology, the ICES may be useful in clinical practice, especially among ED patients. Level of Evidence Level V, cross-sectional descriptive study.